The jack-of-all-trades entrepreneur: innate talent or acquired skill? - Olmo Silva (Institute for the Study of Labor (IZA), 2006)
Cross-sectional tests of the Jack-of-All-Trades theory of entrepreneurship invariably conclude that accumulation of balanced skill-mix across different fields of expertise stimulates entrepreneurship. Yet, none of these considers individual unobservable characteristics which may simultaneously determine skill accumulation and occupational choice. Using panel techniques to control for this, I show that gathering expertise across various subjects does not increase the chances of becoming entrepreneur.
Keywords: M13; J23; J24; 330; entrepreneurship; occupational choice; skills; Unternehmer; Berufswahl; Qualifikation; Theorie; Italien